2016
DOI: 10.1038/srep36552
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Epac1 suppresses mitochondrial fission and reduces neointima formation induced by vascular injury

Abstract: Vascular smooth muscle cell (VSMC) activation in response to injury plays an important role in the development of vascular proliferative diseases, including restenosis and atherosclerosis. The aims of this study were to ascertain the physiological functions of exchange proteins directly activated by cAMP isoform 1 (Epac1) in VSMC and to evaluate the potential of Epac1 as therapeutic targets for neointima formation during vascular remodeling. In a mouse carotid artery ligation model, genetic knockdown of the Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 55 publications
7
42
0
1
Order By: Relevance
“…The results of these studies demonstrate that the migratory and invasive response of VSMCs to PDGF is greatly reduced in the absence of EPAC1, although cAMP and PKA activity is unaltered (502,1088). The suppressed migration of EPAC1-null VSMCs was investigated by Kato and colleagues, demonstrating perturbation of cytosolic Ca 2ϩ release and subsequent dephosphorylation of cofilin in response to PDGF (225,502,1035).…”
Section: Vascular Diseasementioning
confidence: 93%
See 3 more Smart Citations
“…The results of these studies demonstrate that the migratory and invasive response of VSMCs to PDGF is greatly reduced in the absence of EPAC1, although cAMP and PKA activity is unaltered (502,1088). The suppressed migration of EPAC1-null VSMCs was investigated by Kato and colleagues, demonstrating perturbation of cytosolic Ca 2ϩ release and subsequent dephosphorylation of cofilin in response to PDGF (225,502,1035).…”
Section: Vascular Diseasementioning
confidence: 93%
“…Nevertheless, several recent papers have demonstrated that mitochondrial EPAC1 plays important roles in various physiological and pathophysiological conditions. For instance, EPAC1 is implicated in regulation of mitochondrial fission/fusion dynamics and in promoting VSMC prolifera-tion during neointima formation in response to vascular injury (1088). Another study by Brenner and colleagues (1100) suggests that EPAC1 could act as a key effector for mitochondrial cAMP by reducing mitochondrial Ca 2ϩ entry, stabilizing mitochondrial membrane potential, and inhibiting apoptosis in cardiomyocytes.…”
Section: Epac1 Signalosomes At the Cytoskeleton And Other Cellular Locimentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have revealed that EPAC proteins are critically involved in a variety of human diseases such as cancer, inflammation, bacterial and viral infections, central nervous system disorders, energy homeostasis and obesity, and cardiac functions. 814 …”
mentioning
confidence: 99%